How Philip Morris unlocked the Japanese cigarette market: lessons for global tobacco control. Issue 4 (24th November 2004) - Lambert, A; Sargent, J D; Glantz, S A; Ling, P M
Abstract : Background: The Framework Convention on Tobacco Control includes tobacco advertising restrictions that are strongly opposed by the tobacco industry. Marketing strategies used by transnational tobacco companies to open the Japanese market in the absence of such restrictions are described. Methods: Analysis of internal company documents. Findings: Between 1982 and 1987 transnational tobacco companies influenced the Japanese government through the US Trade Representative to open distribution networks and eliminate advertising restrictions. US cigarette exports to Japan increased 10-fold between 1985 and 1996. Television advertising was central to opening the market by projecting a popular image (despite a small actual market share) to attract existing smokers, combined with hero-centred advertisements to attract new smokers. Philip Morris's campaigns featured Hollywood movie personalities popular with young men, including James Coburn, Pierce Brosnan, Roger Moore, and Charlie Sheen. Event sponsorships allowed television access despite restrictions. When reinstatement of television restrictions was threatened in the late 1980s, Philip Morris more than doubled its television advertising budget and increased sponsorship of televised events. By adopting voluntary advertising standards, transnational companies delayed a television advertising ban for over a decade. Conclusions: Television image advertising was important to establish a market, and it has been enhanced using Hollywood personalities. Television advertising bans are essential measures to prevent industry penetration of new markets, and are less effective without concurrent limits on sponsorship and promotion. Comprehensive advertising restrictions, as included in the Framework Convention for Tobacco Control, are vital for countries where transnational tobacco companies have yet to penetrate the market.